Analisis Kesalahan Berbahasa pada 20 Paket Soal Ujian Nasional Bahasa Indonesia SMP 2012/2013 - Rahmawati, Laili Etika; Kartikasari, Fitri; Sukoco, Yudha Wahyu Try (Universitas Muhammadiyah Surakarta, 2014)
This study aimed to analyze the language error on the Bahasa Indonesia National Examination instrument test of the Junior High School in 2012/2013 academic year. The research were qualitative descriptive research. The data analyzed the twenty packets of Bahasa Indonesia National Examination instrument test Secondary School Examination in 2012/2013. Twenty packages National Secondary School Examination in 2012/2013 were qualitative data. Data were collected from a package about twenty National Exams then was analyzed by using the language errors. The types of errors found in language packages about twenty Bahasa Indonesia National Examination in 2012/2013 were faults field of phonology, morphology and syntax. The results showed that language errors that occur in twenty packets Discuss Indonesian National Examination in 2013 as many as 58 data. Data analysis results was presented in accordance with the type of language errors that indicate an error in the twenty language packs Indonesian National Examination in 2013, both in the areas of phonology, morphology, and syntax.